Floorball as a new sport : case study : Bulgaria as a floorball destination from insider's point of view - Bliznakova, Rositsa (2011)
Floorball is a relatively new but quickly growing sport. Together with its development and spreading its importance grows as well. However previously conducted research on floorball from its managerial point of view is rare, especially on an international scale. The present investigation makes an attempt to fill this gap in a holistic manner. It explores the research problem of finding the potentials of floorball as a sustainably successful sport – worldwide and in the case country, Bulgaria.